Polymyxin Combinations Combat Escherichia coli Harboring mcr-1 and blaNDM-5: Preparation for a Postantibiotic Era - Zackery P. Bulman (American Society for Microbiology, 2017)
ABSTRACT The rapid increase of carbapenem resistance in Gram-negative bacteria has resurrected the importance of the polymyxin antibiotics. The recent discovery of plasmid-mediated polymyxin resistance (mcr-1) in carbapenem-resistant Enterobacteriaceae serves as an important indicator that the golden era of antibiotics is under serious threat. We assessed the bacterial killing of 15 different FDA-approved antibiotics alone and in combination with polymyxin B in time-killing experiments against Escherichia coli MCR1_NJ, the first reported isolate in the United States to coharbor mcr-1 and a New Delhi metallo-β-lactamase gene (blaNDM-5). The most promising regimens were advanced to the hollow-fiber infection model (HFIM), where human pharmacokinetics for polymyxin B, aztreonam, and amikacin were simulated over 240 h. Exposure to polymyxin B monotherapy was accompanied by MCR1_NJ regrowth but not resistance amplification (polymyxin B MIC from 0 to 240 h [MIC0h to MIC240h] of 4 mg/liter), whereas amikacin monotherapy caused regrowth and simultaneous resistance amplification (amikacin MIC0h of 4 mg/liter versus MIC240h of >64 mg/liter). No MCR1_NJ colonies were observed for any of the aztreonam-containing regimens after 72 h. However, HFIM cartridges for both aztreonam monotherapy and the polymyxin B-plus-aztreonam regimen were remarkably turbid, and the presence of long, filamentous MCR1_NJ cells was evident in scanning electron microscopy, suggestive of a nonreplicating persister (NRP) phenotype. In contrast, the 3-drug combination of polymyxin B, aztreonam, and amikacin provided complete eradication (>8-log10 CFU/ml reduction) with suppression of resistance and prevention of NRP formation. This is the first comprehensive pharmacokinetic/pharmacodynamic study to evaluate triple-drug combinations for polymyxin- and carbapenem-resistant E. coli coproducing MCR-1 and NDM-5 and will aid in the preparation for a so-called “postantibiotic” era. IMPORTANCE A global health crisis may be on the horizon, as the golden era of antibiotics is under serious threat. We recently reported the first case in the United States of a highly resistant, Escherichia coli so-called “superbug” (MCR1_NJ), coharboring two of the most worrying antibiotic resistance genes, encoding mobile colistin resistance (mcr-1) and a New Delhi metallo-β-lactamase (blaNDM-5). Worryingly, the medical community is vulnerable to this emerging bacterial threat because optimal treatment strategies are undefined. Here, we report the activity of an optimized combination using simulated human doses of commercially available antibiotics against MCR1_NJ. A unique triple combination involving a cocktail of polymyxin B, aztreonam, and amikacin eradicated the MCR-1- and NDM-5-producing E. coli. Each antimicrobial agent administered as monotherapy or in double combinations failed to eradicate MCR1_NJ at a high inoculum. To our knowledge, this is the first study to propose 3-drug therapeutic solutions against superbugs coharboring mcr-1 and blaNDM, seeking to prepare clinicians for future occurrences of these pathogens.